Assessment of the Soil Buffer Capacity in the Sea of Azov Basin Under Heavy Metal Pollution - Minkina, Tatiana; Nevidomskaya, Dina; Sherbakov, Aleksey; Chaplygin, Victor; Litvinov, Yurii; Kravtsova, Natalia; Bren, Dmitry; Lobzenko, Ilia (KnE Life Sciences, 2022)
Heavy metals (HM) are among the most hazardous soil pollutants. The intensity of accumulation and distribution of HM in soils directly depends on the ecological conditions of pedogenesis and its buffering properties. At the same time, a significant accumulation of HM in the soil as a result of anthropogenic impacts reduces the buffering capacity of the soil and its resistance to pollution. The purpose of this work was to assess the buffering capacity of soils to HM pollution in the Don River delta and the coast of the Taganrog Bay of the Sea of Azov undergoing the great anthropogenic impact. The buffer capacity of experimental soils was carried out using the Il’in’s method (1995), based on the calculation of the inactivation ability of soils: organic matter, clay fraction (particle size < 0.01 mm), carbonates, sesquioxides, and pH. The content of HM was compared with soil Clarke and the maximum permissible concentration of HM in soils accepted in the Russian Federation. It was found that the experimental soils could be ordered by buffer capacity value as following (in decreasing order): haplic chernozem ≥ alluvial-meadow light loamy ≥ solonchak > alluvial-meadow sandy and sandy loamy > sandy primitive soil ≥ stratified alluvial soil. Keywords: trace elements, contamination, impact territories